Insights into chemometric algorithms for quality attributes and hazards detection in foodstuffs using Raman/surface enhanced Raman spectroscopy. Issue 3 (21st April 2021) - Wang, Jingjing; Chen, Quansheng; Belwal, Tarun; Lin, Xingyu; Luo, Zisheng
Abstract: Raman spectroscopy and surface‐enhanced Raman spectroscopy (SERS) have been extensively explored in the design of accurate, transparent, and conclusive food safety and quality control assays. Its hyphenation with chemometric algorithms is instrumental in securing safe food campaigns. To provide valuable recommendations and meet the growing demands for food screening, the current study begins with a brief description of the Raman spectroscopy and SERS theory followed by a comprehensive overview of spectral preprocessing, qualitative algorithms, variable selection methods, and quantitative algorithms. The review emphasizes on the importance of food monitoring practices using multivariate regression models. The applicability of the distinct chemometrics modes toward monitoring pesticide, food and illicit additives, heavy metals, pathogens, and its metabolites in Raman spectroscopy and SERS is covered in dairy, poultry, oil, honey, beverages, and other selected food matrices. Its pertinence toward classification and/or discrimination in food quality and safety monitoring and authentication is examined. Finally, it also complies with the limitations, key challenges, and prospects. The chemometrics processing spectra implemented with simpler or no complicated sample pretreatment step make Raman spectroscopy/SERS technique a potential approach that is expected to achieve simultaneous and fast detection of multiple analytes in food matrices.